WEB APPLICATION DESIGN ALLIZE MURDER PHOTOWORK USING MACROMEDIA DREAMWEAVAER 8.0 - Andhi Hariyanto; Yudi Irawan Chandra (Jurnal Sistem Informasi, 2010)
Website is one of the forms of media found on the Internet. Currently thewebsite is widely used by the general public or an organization to meet thedemand for information on today. With the website is expected many users canreceive information with a quick time and also accurately without the cost of amajor. Generally, the website is also used by most large corporations to conductpromotions or offers the goods they produced, as well as photography services.Usually in the process of promoting its photographers only use sheets orpamphlets from mouth to mouth, but now the Internet media into a very precisesulusi in doing that process. In this scientific writing process not only offerthese services in the promotion process but you can also order a photographictools to begin studying to become a professional photographer will be shownentirely using Macromedia Dreamweaver 8.0.